2022
DOI: 10.31083/j.ceog4902048
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial receptivity and PCOS; endometrial gene expression specificities — literature review

Abstract: Objectives:The purpose of this review is to provide an overview of existing studies on the specificities of gene expression in the endometrium in PCOS and possible molecular mechanisms linking those specificities with reproductive and obstetric consequences of PCOS. Mechanism: Polycystic ovary syndrome (PCOS) is a complex disorder combining features of reproductive, metabolic, and psychological disturbances. The effect of metabolic, inflammatory, and endocrine abnormalities on ovulatory function and oocyte qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…In the study of Crespi (3), an increase in spontaneous abortion was reported in women with PCOS. Contrary to the above studies, the study by Alebić (1) showed that the rate of abortion in PCOS syndrome is probably not different from the control group. The difference could be because pregnant women with PCOS in previous studies were older than the control group, as age also plays a destructive role in increasing pregnancy complications (6).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In the study of Crespi (3), an increase in spontaneous abortion was reported in women with PCOS. Contrary to the above studies, the study by Alebić (1) showed that the rate of abortion in PCOS syndrome is probably not different from the control group. The difference could be because pregnant women with PCOS in previous studies were older than the control group, as age also plays a destructive role in increasing pregnancy complications (6).…”
Section: Discussionmentioning
confidence: 69%
“…In endometriosis, the endometrial tissue of the uterus extends out to the pelvic space,peritoneum and on to the organs like ovaries, intestines and the bladder. The disease spectrum is vast and ranges from large endometrioma cysts to small lesions on the pelvic organs, creating significant adhesions in the uterus, bladder and intestine and disrupting the anatomy of the pelvis (1)(2)(3). The disease treatment is still associated with many problems.…”
Section: Introductionmentioning
confidence: 99%
“…In women suffering PCOS, endometrial receptivity has been postulated to be affected via several mechanisms: (1) sustained androgenic exposure due to the abberant hormonal milieu [69,70], (2) metabolic alterations that regulate decidualization [71], (3) compromised PR functions led to total failure of the uterus in supporting embryo implantation [72], and (4) altered intrauterine microenvironment via deregulation of local inflammatory mediators [73,74]. In clinical practice, PCOS is related to a higher risk of miscarriage and adverse pregnancy outcomes [75], though its effect on IVF and FET cycles remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In this literature review, Alebić has discussed the specificities of endometrial receptivity in PCOS patients focusing primarily on the association between features of PCOS and endometrial gene expression changes observed in these patients. The paper targeted the clinicians who are interested in possible mechanisms of lower clinical and ongoing pregnancy rates observed among patients with PCOS [4].…”
mentioning
confidence: 99%